Unravelling Philosophy of Fear: A Move to Overcoming Negative Fear - Eneyo, Michael (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
Through history, fear has been conceived as something negative with the potency to kill human dreams and potential. Thus, the discussion on fear, as shown in this work regarding the Greek philosophers before the systematic study of “the philosophy of fear” emerged, was saturated with negative ideas about fear. In this work, I traced the origin of fear studies to the ancient Greek philosophers. I acknowledged that this does not imply that other worldviews were not concerned about fear, but there are no or little pieces of literature available as evidence. I argued that the Greek scholars' perspectives on fear were mostly animistic and reductionistic in nature, while acknowledging their negative undertones. Despite agreeing with Subba (2014) on the notion of positive fear, I showed how it has spurred industrial and scientific progress in human civilisation. Likewise, since fear is an existential threat to humans throughout civilizations, I also show how the COVID-19 pandemic and the Russo-Ukrainian War have engaged the world negatively in a “game of fear” during the early decades of the 21st century. Lastly, against the backdrop of modern challenges that engender fear in the world, I proposed two principles that can be used in overcoming negative fear: “the acquaintance method” and “the love-fear method.” This work was carried out majorly with the method of content analysis—examining the central ideas of some existing literature relating to “fear studies” and the “philosophy of fear”, while also using the deductive method of philosophy to propose the two principles as solutions to the problem of fear.